A study of South African aquatic Hyphomycetes - Greathead, Sarah Kathleen (Rhodes University, Faculty of Science, Botany Department, 1962)
1, Eighteen species of aquatic Hyphomycetes are recorded from South Africa for the first time. All except two of these can be assigned to described species. The other two are new species of Articulospora and Anguillospora and are described in this thesis. Three unidentified spore types, an "Articulospora" type and "Anguillospora" type and a Y-shaped spore are also described. 2. Spore development in ten species is described. 3. A key to the fungi described in this thesis is given. 4. General notes on the ecology of these fungi and a table recording the fungi found in the Eastern Cape Province of South Africa, their distribution within the localities and the nature of the material on which they are growing are given. 5. The gross characteristics of plate cultures of six species, five growing on malt agar, Czapek agar, plain agar and maize agar and one on malt agar only are described. 6. Growth of four species in liquid culture using the Czapek-Dox medium is reported. 7. The results of an investigation into the effect of variations in temperature and medium on the growth of plate cultures of five species are analysed, discussed and conclusions are drawn. 8. Growth of certain isolates of four species on twigs is described.
Keywords: Hyphomycetes -- South Africa; Aquatic fungi -- South Africa